SpatialEase: Learning Language through Body Motion - Edge, Darren; Cheng, Kai-Yin; Whitney, Michael (CHI 2013 Conference on Human Factors in Information Systems, 2013)
Games that engage both mind and body by targeting users’ kinesthetic intelligence have the potential to transform the activity of learning across a wide variety of domains. To investigate this potential in the context of second language learning, we have developed SpatialEase: a Kinect game for the body-based learning of language that is grounded in space and motion. In this game, learners respond to audio commands in the second language by moving their bodies in space, while a game mechanic based on distributed cued-recall supports learning over time. Our comparison of SpatialEase with the popular Rosetta Stone software for learner of Mandarin Chinese showed similar learning gains over a single session and generated several key implications for the future design of mixed-modality learning systems.